Occupational health and safety specialist in Croatian and Portuguese legislation - Šantek, Domagoj (Array, 2020)
The domain of occupational safety and health at work is put for regulation through directives by founding agreements. This means that the institutions of the European Union prescribe minimum standards of safety and health at work through directives and Member States need to accomplish goals that a particular directive pursues. At the same time, this means that each Member State can also set stricter standards than the ones prescribed through directives and for this reason some differences in regulations of individual Member States can be noticed. In this paper, authors focus on the role of occupational safety specialist and the manner in which the Republic of Croatia and the Portuguese Republic, in their legislation, prescribe obligations of the employer in terms of contracting the performance of occupational health and safety tasks with an occupational safety specialist or an external service. Authors furthermore examine required conditions which occupational safety specialist must meet to perform those tasks. Apart from outlining the Croatian and Portuguese legislation, authors also present and define fundamental similarities and differences in the regulations within this domain of security legislation.